Gerakan Sewu-Sewu Ae: Peran Nyata Pemuda Mengarungi Pandemi - Jannah, Salsabilah Shofiyatul; Alamsyah, Anrico; Yunarko, Dika Ifanda (Laboratorium Sosiologi FISIP Universitas Jember, 2022)
This article aims at explaining Sewu-Sewu Ae movement which is held by the youth in Madiun city during the Pandemic of COVID-19. It is a movement initiated from some concerns from the youth toward what happened to society especially in the time of PPKM period. This is a participatory approach as one of the authors is a pioneer of the movement. The research objective is to analyze several fundamental values, innovations, operational systems, and evaluations in the Sewu-Sewu Ae movement. Data were collected using observation, documentation, and interviews. The results of the study found that one of the biggest challenges of the society was economic difficulty. Although government has provided solutions, the implementation was complicated by the system. Reflecting from this reality, the youth took a step to take roles on this matter. During the pandemic, philanthropy-based social movements are increasingly prevalent in several cities, for example, the